The County: The "Dark Continent" of American Politics - Gilbertson, Henry S. (Salt Lake City, UT : Project Gutenberg, 2022)
"The County: The 'Dark Continent' of American Politics" by Henry S. Gilbertson is a political analysis written in the early 20th century. This work dives into the often overlooked yet crucial role of county governments in the broader landscape of American democracy. It explores the inefficiencies, complexities, and the unique challenges that county governments face, suggesting that a deeper understanding of these local administrations could illuminate fundamental issues persisting within the democratic system. The opening of the volume introduces the author's intent to shed light on the subtleties of county governance, highlighting a disconnect between the electorate's complacency and the actual workings of these political structures. Gilbertson notes a lack of attention given to the county's role in democracy, as citizens generally exhibit indifference toward county issues, often relying on old traditions without sufficient scrutiny. This disconnect is illustrated through concrete examples of misconduct and inefficiency within various counties, revealing systemic issues that underscore the need for serious reform and renewed engagement from the citizenry. The author argues that a critical examination of county governments is essential for enhancing democratic accountability and effectiveness in local governance. (This is an automatically generated summary.)
Release date is 2022-02-07
deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: County government -- United States